Epilepsy and Seizure-Related Hospital Admissions to an Australian Neurology Unit: A Prospective Observational Study. Issue 1 (1st October 2020) - Khoo, Anthony; Frasca, Joseph; Whitham, Emma
Abstract: This study provides contemporary data on patients admitted to a Neurology unit with seizures, the majority of whom have a diagnosis of epilepsy. There were 278 hospital presentations with seizure during the 6-month study period, with 60 admissions to the Neurology unit included for analysis. Provoking factors were identified in 40%, with poor medication adherence the commonest precipitant. CT-brain had low diagnostic yield in patients with epilepsy presenting with seizure and should be reserved for those with further indications for imaging. Patients with drug-resistant epilepsy comprised 54% of admissions suggesting management strategies in this cohort can be further optimized.